Trends and emerging issues on Islamic banking performance: bibliometrics analysis - Aprizal, Anggi; Wiranatakusuma, Dimas Bagus (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to conduct a systematic review of the literature on Islamic banking performance. Method – This research analyses trends and developments in the field using the systematic literature review and mapping study approaches. A total of 56 articles were selected from an initial pool of 130 articles sourced from ScienceDirect and Scopus, using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method. Findings – The findings reveal that trend analysis, density visualization using VosViewer, and mapping studies indicate that research on Islamic banking performance remains dominated by traditional topics such as efficiency, financial performance, and risk management. The primary indicators include return on assets (ROA), return on equity (ROE), non-performing financing (NPF), and loan-to-deposit ratio (LDR). However, studies on Islamic bank resilience, fintech integration, and their role in developing economies remain limited. A more holistic approach is needed to address challenges and opportunities in the digital era. Implications – The implications of this study highlight the importance of policies that support digital innovation while adhering to Sharia principles. Additionally, this study identifies future research opportunities, including the resilience of Islamic banks during crises, the impact of digitalization on efficiency, the contribution of Islamic banking to the green economy, and the influence of regulations on Islamic bank performance. Ultimately, this study provides valuable insights into the trends, challenges, and opportunities facing Islamic banking in an evolving global economic landscape.